Growth effects of capital inflows and investment in Nigeria - Fredrick Ikpesu (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
The aim of this study was to ascertain the growth effects of capital inflows using investment as a transmission channel between the periods 1981 to 2016 in Nigeria. The study employed the least square regression method to analyse the data. The outcome of the research indicates that capital inflows have a positive and significant effect on the growth of the Nigeria economy. This imply that foreign capital inflows have contributed to the economic growth of the country. Furthermore, the research output also showed that domestic investment has a positive and significant effect on Nigerian economic growth. From the findings of the study, it is concluded that capital inflow and domestic investment has positively contributed to the growth of Nigeria economy. The findings of this study posed significant policy direction. Firstly, the study emphasized the need for government and policy-makers to attract more inflow of foreign capital into the country but the detrimental effect of huge capital inflow into an economy should also be considered. Secondly, the government should determine the optimal capital inflow that would propel investment and growth in the country. Thirdly, the government should strengthen the macroeconomic fundamentals by deepening structural reforms so as to ensure sustainable capital inflows into the country. Finally, the government should create an enabling environment by providing the needed infrastructural facilities in a bid to attract foreign investors and encouraging domestic investment in the country.
Keywords: F21; P33; 330; Capital inflow; investment; growth; augmented solow growth model; Nigeria